Root Cause Analysis Tool Of Accident Toward Safer Delivery Experience Of P-Hailers - Muhammad Amir Ashyraf, Noor Azli (2025)
In the contemporary era marked by rapid technological advancements and the widespread impact of the global pandemic, the gig economy has arisen, significantly reshaping the commercial food and parcel delivery sector. This transformation is observed in Malaysia, where the efficiency of delivery systems has become a cornerstone for e-commerce, ensuring the timely distribution of goods to consumers. The emergence of various courier service providers, such as Pos Laju, J&T, Easy Parcel, FoodPanda, and Grab, is a testament to the growing demand for p-hailing sectors, which have become indispensable to Malaysia’s e-commerce industry. Despite their critical role, the gig economy’s swift expansion, characterized by its flexible work hours and freelance nature, has introduced a unique set of challenges for occupational safety and health (OSH). This study explores the pressing need for enhanced safety management in the p-hailing sector, focusing on the development of a Root Cause Analysis (RCA) tool aimed at ensuring smooth and safe delivery operations. The urgency for such innovation is underscored by the rising incidence of accidents involving p-hailing riders, posing risks to their safety and affecting service reliability and customer trust. The proposed RCA tool provides a systematic framework and a digitalized template for database collection to identify, analyze, and address the root causes of accidents. The tool is designed to mitigate accident occurrences and foster safer delivery practices. To validate the content of the RCA tool, a Content Validity Index (CVI) assessment was conducted, involving experts in occupational safety and health and industry professionals which are related and well known about most contributing factor of accident among p-hailing industry. The CVI results in the range of 0.80-1.00 indicated a high level of agreement on the tool's relevance and clarity, affirming its validity for use in the p-hailing sector. Additionally, a case study was conducted with selected p-hailing company to test the tool's functionality in real-world scenarios by using the System Usability Scale (SUS) and open-ended interview. Participants or user of the RCA tool were chosen based on their position in the management of the p-hailing company to give the feedback and opinion about the usability and experience from using that tool. User experience and satisfaction with the RCA tool were evaluated by using the System Usability Scale (SUS). The SUS assessment yields a mean of score 0.70, indicating good rating scale in term of usability of the tool. Participants highlighted the tool's intuitive interface, ease of use, and practical application in identifying accident causes and improving safety measures. These findings validate the tool's potential to support safety management in the phailing industry. By systematically analyzing data and identifying patterns, the RCA tool enables organizations to discern trends and common factors leading to accidents. This facilitates targeted interventions and prevention strategies, fostering a holistic approach to safety management. The implementation of the RCA tool is expected to significantly reduce accidents, enhance the delivery experience for p-hailers, and contribute to the overall safety and sustainability of the gig economy in Malaysia.